Pengaruh Pemberian Teknik Relaksasi Genggam Jari terhadap Perubahan Kecemasan Pasien dengan Pasien Pre Operasi di RSUD Batang - Johan Mukhibul Ahkam; Dwi Retnaningsih (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Patients undergoing surgery often experience preoperative anxiety due to concerns about the outcome, pain, and the risk of complications. Uncontrolled anxiety can affect the patient's physiological and psychological condition and slow the recovery process. One non-pharmacological effort that can be used to reduce anxiety is the finger-holding relaxation technique, a simple method that can help balance emotions and provide a sense of calm. To determine the effect of the finger-holding relaxation technique on changes in preoperative anxiety levels in patients at Batang Regional General Hospital. Method: This study used a descriptive case study approach. The respondents were four patients who were about to undergo surgery and were experiencing anxiety. The intervention was conducted for approximately 15 minutes using the finger-holding relaxation technique. Anxiety levels were measured before and after the intervention using the Hamilton Anxiety Rating Scale (HARS). All respondents experienced a decrease in anxiety levels after the intervention. The average reduction in anxiety scores was 7.25 points. Before the intervention, two patients experienced severe anxiety and two patients experienced moderate anxiety. After the intervention, two patients experienced mild anxiety and two others experienced a decrease to moderate levels. This indicates that finger-holding therapy has a positive effect on reducing preoperative anxiety in patients. The finger-holding relaxation technique has been proven effective in reducing preoperative anxiety in patients. This intervention can be used as a simple, safe, and easy-to-implement non-pharmacological therapy alternative for nurses to improve patient psychological comfort.